The diagnostic and prognostic value of coronary CT angiography in asymptomatic high-risk patients: a cohort study. Issue 1 (12th August 2014) - Plank, Fabian; Friedrich, Guy; Dichtl, Wolfgang; Klauser, Andrea; Jaschke, Werner; Franz, Wolfgang-Michael; Feuchtner, Gudrun
Abstract : Objective: To prospectively assess the value of coronary CT angiography (CTA) in asymptomatic patients with high 'a priori' risk of coronary artery disease (CAD). Methods: 711 consecutive asymptomatic patients (61.8 years; 40.1% female) with high 'a priori' risk of CAD were prospectively examined with a coronary calcium score (CCS) and CTA. Coronary arteries were evaluated for atherosclerotic plaque (non-calcified and calcified) and stenosis (mild <50%, intermediate 50–70% or high-grade >70%). Coronary Segment Involvement Score (SIS, total number of segments with plaque) and nc (non-calcified) SIS were calculated. Primary end points were major adverse cardiac events (ST-elevation MI, non-ST-elevation MI and cardiac death); secondary end points were coronary revascularisation and >50% stenosis by invasive angiography. Results: Of 711 patients, 28.3% were negative for CAD and 71.7% positive (CAD+) by CTA (15.6% had plaques without stenosis, 23.9% mild, 10.7% intermediate and 21.5% high-grade stenosis). CCS zero prevalence was 306 (43%), out of those 100 (32.7%) had non-calcified plaque only. Mean follow-up period was 2.65 years. MACE rate was 0% in CAD negative and higher (1.2%) in CAD positive by CTA. Coronary revascularisation rate was 5.5%. Patients with SIS ≥5 had an HR of 6.5 (95% CI 1.6 to 25.8, p<0.013) for MACE, patients with ncSIS ≥1 had an HR of 2.4 (95% CI 1.2 to 4.6, p<0.01) for secondary end point. The sensitivity of CTA for stenosis >50% compared with invasive angiography was 92.9% (95% CI 83.0% to 98.1%). Negative predictive value of CTA was 99.4% (95% CI 98.3% to 99.8%) for combined end points. Conclusions: CAD prevalence by CTA in asymptomatic high-risk patients is high. CCS zero does not exclude CAD. CTA is highly accurate to exclude CAD. Total coronary plaque burden and nc plaques, even if only one segment is involved, are associated with an increased risk of adverse outcome.